Surgical treatment of proximal humerus fractures with intramedullary nail - Maniscalco, Pietro; Ciatti, Corrado; Gattoni, Serena; Puma Pagliarello, Calogero; Quattrini, Fabrizio (Lo Scalpello - Journal, 2021)
Introduction. Proximal humerus fracture is the most common fracture of the shoulder gir- dle, accounting for approximately 4-7% of all fractures. The aim of this study is to provide surgeons safe and effective surgical solutions, minimizing the risk of complications.Materials and methods. We retrospectively analyzed all 3-fragment proximal humerus frac- tures, treated between January 2017 and December 2018 with the Diphos® short intramedullary nail (Lima Corporate®, San Daniele del Friuli, Italy). 33 patients, 19 men (57.6%) and 14 women (42.4%), were included; average age was 68.4 years (min. 63 - max. 78, SD 3.67).Results. Hospitalization was 6.27 ± 2.87 days (3.6 days before undergo surgery, 2.7 days after). Mean surgical time was 27.36 ± 8.49 minutes. On average, patients healed after 78.36 days. We registered 10 complications: 4 malunion (12.1%), 2 screw-cut outs (6.1%), 1 delayedunion (3.0%), 1 cuff lesion (3.0%), 1 loss of reduction (3.0%), and 1 intraoperative fracture(3.0%). Overall re-operation rate was 6.1%.Conclusions. During surgery, it is crucial to choose the right entry point when placing the nail. Failing at this level can lead to intraoperative and postoperative complications, in addi- tion to worse clinical outcomes.